How and why Covid-19 has affected our perception of Moral Enhancement? - Palazzani, Laura; Garasic, Mirko (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
The explosion of the Covid-19 pandemic era -with the resulting chaos and stress that liberal democracies have suffered in managing to balance out individual freedoms and public health have brought new verve into the discussion concerning a vast scale implementation of moral enhancers so to “only” ensure that citizens will comply with what is best of the overall population. In other words, the argument is: if people are unable to rationally follow through with the idea of responsibility towards oneself and others, we might be morally obliged to use the biochemical tools in our hands to “push” them to do “the right thing”. Though tempting at first glance -especially in the midst of an epochal crisis that will revolutionize our interaction with others forever- we want to argue that caution should abound when depicting such a positive portray of what we could achieve -while missing out on what we might undermine in our value system, as well as in our political understanding of authority, power and experts. Starting with an analysis of the historical discussion centred on Moral Enhancement, we will move forward into analysing the specific impact that Covid-19 has had on the arguments in favour of it -and we will attempt to provide a response.